Doing Migration in Adulthood: Learning to Engage With the Canadian Experience Discourse - Bernhard, Michael (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2023)
Among the well-documented challenges faced by newcomers to Canada is the possession of Canadian experience (CE) as a prerequisite for successful entry into the labour market. Building on discussions that highlight the exclusionary functions of the CE discourse, this paper employs Dewey’s concept of active and passive experience and applies a doing migration framework in order to study how individuals interact with this discourse. Empirically, this paper draws on narrative interviews conducted with individuals with tertiary education who moved to Canada in adulthood. Using the documentary method, I identified three modes of engagement with CE discourse as replay and readjust, reset and move forward, and research and pro-act. Results illuminate the various forms of engagement, highlighting active, passive, and relational dimensions of doing migration. Concluding, I argue that such relational perspective has implications for adult education and the approaches taken to support individuals as they settle into life in Canada, as well as for theoretical perspectives on learning.